Designing world class e-learning : how IBM, GE, Harvard Business School, and Columbia University are succeeding at e-learning - Schank, Roger C. (New York : McGraw Hill Education, 2002)
Explores online learning and explains how Web-based simulations and role-playing scenarios can be used to radically rethink the process of providing training in organizations. This work explores the ways in which the Web can improve the content of training programs, by placing employees in virtual work environments, that allow them to experiment.
Includes index.
Keywords: Employees -- Training of -- Case studies